REVISIÓN TAXONÓMICA DEL GÉNERO PSYRASSA PASCOE (COLEOPTERA: CERAMBYCIDAE) - Toledo, Víctor H. (Instituto de Ecología, A.C., 2005)
The taxonomy of the genus Psyrassa is revised and updated. Thirty two valid species are recognized in the genus. Six species are new to science: Psyrassa angelicae sp. nov. from Mexico, P. cerina sp. nov. from Guatemala and Honduras, P. chamelae sp. nov. from Mexico, P. clavigera sp. nov. from Costa Rica and Panama, P. graciliatra sp. nov. from Honduras, and P. proxima sp. nov. from Mexico, Guatemala and Honduras. Psyrassa texana Schaeffer is synonymized under P. castanea Bates, P. punctulata Bates is synonymized under P. cribricollis Bates and P. wappesi Chemsak and Noguera is synonymized under Aneflomorpha giesberti Chemsak and Linsley, all are new synonymies. It includes adult male and female diagnoses and descriptions (except P. aliena, P. rufofemorata and P. chamelae sp. nov. known only from males), detailed distribution records and an illustrated key to separate all species, along with drawings and photographs.